The Influence of Entrepreneurial Motivation and Family Business on the Entrepreneurial Decision of Generation Z Alumni of the University of Lampung - Oktaviani, Melani; RR. Erlina (Economics and Digital Business Review, 2025)
Entrepreneurs are people with a high spirit of creativity and innovation in their lives, so they must have high entrepreneurial motivation to become successful entrepreneurs. Entrepreneurial motivation is also important in generating interest in entrepreneurship, especially in running a family business. At the University of Lampung, only 1,732 of the 25,228 graduates in 2019-2023 became entrepreneurs, and just 64 became entrepreneurs to continue the family firm. This study examines if entrepreneurial desire and family business impact Generation Z Lampung University alumni's entrepreneurial decisions. Generation Z University of Lampung graduates provided 325 eligible samples for this quantitative study. After questionnaire data collection, the study was assessed for validity, reliability, and normalcy using simple linear regression and the T test. The study and discussion show that (1) entrepreneurial motivation positively and significantly affects Generation Z Lampung University graduates' entrepreneurial choices. Lampung University graduates' entrepreneurial readiness depends on their drive for independence, self-realization, and other motivators. (2 Family company positively impacts University of Lampung Generation Z alumni's entrepreneurial choices. The positive effect implies that the family gives respondents moral support and motivation to grow their company.